DEVELOPMENT OF INTERNET OF THINGS (IoT) BASED FLOOD EARLY WARNING TOOLS - Rezky Fadilah; Ruslan, Ruslan; Imran, Al (Journal of Electrical Engineering and Informatics, 2024)
This research is research and development (R&D) using a prototype development model. This research aims to develop an early flood warning system using the Telegram application as an early sender of information, if the water level has reached a predetermined limit. Test results: In terms of Functionality and Usability, the results of the functionality feasibility percentage were 100% and as many as 20 respondents or 100% assessed that the tool developed based on the Usability context was at 100% in the very good category. The detection speed test results show that the detection speed on the device is around 2-3 s and the speed of sending information on Oled is around 2-3 s and the speed of sending information to Telegram is 2-3 s.